An investigation into the perspectives of Irish primary school teachers on the use of the Content and Language and Integrated Learning approach for teaching Irish. - Ní Bhrolcháin, Nóirín (Marino Institute of Education, 2021)
The teaching of Irish in primary schools and the best ways in which to do so is a highly discussed topic within the Irish education system. There are varying opinions and attitudes towards the teaching of Irish. The new Primary Language curriculum was introduced in 2015 which encourages an integrated and active approach to language teaching for English and Irish. In 2019, the Content and Language Integrated Learning pilot programme was introduced by the Department of Education and Skills in 2019. For these reasons, new and integrated approaches to teaching Irish have become topical within the Irish education system. The researcher chose to focus on examining teachers’ perspectives on using the Content and Language Integrated Learning (CLIL) approach to teach Irish and investigating whether the CLIL approach was an effective method of language teaching in the experiences of chosen participants. Qualitative data was collected through semi-structured interviews with a number of participants who had varying experiences of using the CLIL method. These experiences and perspectives were then analysed and related to existing literature in the findings chapter of the study. Recommendations for future implementation of CLIL in Irish primary schools are made in the Conclusion chapter of the study.
Keywords: Irish language; Irish Primary Schools; Teaching; Primary Language curriculum; Content and Language Integrated Learning (CLIL) approach; Irish language; Primary education; Teaching; Ireland